Structural Damage Detection of A Steel-Truss Railway Bridge Using its Dynamic Characteristics - T. Susanto; A. Budipriyanto (IPTEK Journal of Proceedings Series, 2014)
Many steel truss rail bridges in Indonesia were built decades ago. To assure that bridge structure is in-service conditions, periodic monitoring is required, thus structural health of the bridge can be assessed and sudden collapse of the structure can be avoided. In health monitoring of structure, structural damage detection methods are frequently required so that damaged/weak element of the structure can be identified and technique for repairing it can be determined. In this paper, structural damage detection method of steel truss bridge is discussed. The method applied in this study used vibration characteristics of the structure for detecting structural damages occurred in the structure. The method was utilized to identify simulated damages occurred in a steel-truss railway bridge located in Porong East Java. The bridge has span of 30 meters and it was built during the era of Dutch colonization. The structure was modeled numerically utilizing CSI Bridge v15 computer software for facilitating in obtaining its dynamic characteristics. Results of this study showed that the method could identify precisely the existence of damage took place in the structure.